A comprehensive and integrative re-description of Synchaeta tremula (Müller, 1786) and the newly rediscovered Synchaeta tremuloida Pourriot, 1965 (Rotifera: Synchaetidae) - Wilke, Tanja; Ahlrichs, Wilko H.; Bininda-Emonds, Olaf R.p. (Zootaxa, 2017)
In this paper, we focus on the two morphologically similar species Synchaeta tremula (Müller, 1786) and Synchaeta tremuloida Pourriot, 1965. This study records one of the first detections of the latter species since its initial description and clarifies its uncertain taxonomic status. Using an integrative approach combining morphological data (from light and scanning electron microscopy) with molecular and ecological data, we present re-descriptions of S. tremula and S. tremuloida and confirm their status as separate species. Finally, we also provide a unique character set that can be readily applied to unambiguously identify each species using easily observable features.